Design and development of a smart picosatellite - Kuah, Zhen Keng. (2012)
The option of miniaturising satellites has been thoroughly explored because of its cost saving potential. Building a satellite from Commercial Off-The-Shelf (COTS) products not only further pushes idea of saving costs, it also saves invaluable time which could have been put into the research and manufacturing of the hardware components.